The clinical and cost-effectiveness of elective primary total knee replacement with PAtellar Resurfacing compared to selective patellar resurfacing: a pragmatic multicentre randomized controlled Trial (PART): the clinical and cost-effectiveness of elective primary total knee replacement - Adam Boon; Elizabeth Barnett; Lucy Culliford; Rebecca Evans; Jessica Frost; Zastra Hansen-Kaku; William Hollingworth; Emma Johnson; Andrew Judge; Elsa M. R. Marques; Andrew Metcalfe; Patricia Navvuga; et al. (Bone & Joint Open, 2024)
Aims: During total knee replacement (TKR), surgeons can choose whether or not to resurface the patella, with advantages and disadvantages of each approach. Recently, the National Institute for Health and Care Excellence (NICE) recommended always resurfacing the patella, rather than never doing so. NICE found insufficient evidence on selective resurfacing (surgeon’s decision based on intraoperative findings and symptoms) to make recommendations. If effective, selective resurfacing could result in optimal individualized patient care. This protocol describes a randomized controlled trial to evaluate the clinical and cost-effectiveness of primary TKR with always patellar resurfacing compared to selective patellar resurfacing. Methods: The PAtellar Resurfacing Trial (PART) is a patient- and assessor-blinded multicentre, pragmatic parallel two-arm randomized superiority trial of adults undergoing elective primary TKR for primary osteoarthritis at NHS hospitals in England, with an embedded internal pilot phase (ISRCTN 33276681). Participants will be randomly allocated intraoperatively on a 1:1 basis (stratified by centre and implant type (cruciate-retaining vs cruciate-sacrificing)) to always resurface or selectively resurface the patella, once the surgeon has confirmed sufficient patellar thickness for resurfacing and that constrained implants are not required. The primary analysis will compare the Oxford Knee Score (OKS) one year after surgery. Secondary outcomes include patient-reported outcome measures at three months, six months, and one year (Knee injury and Osteoarthritis Outcome Score, OKS, EuroQol five-dimension five-level questionnaire, patient satisfaction, postoperative complications, need for further surgery, resource use, and costs). Cost-effectiveness will be measured for the lifetime of the patient. Overall, 530 patients will be recruited to obtain 90% power to detect a four-point difference in OKS between the groups one year after surgery, assuming up to 40% resurfacing in the selective group. Conclusion: The trial findings will provide evidence about the clinical and cost-effectiveness of always patellar resurfacing compared to selective patellar resurfacing. This will inform future NICE guidelines on primary TKR and the role of selective patellar resurfacing. Cite this article: Bone Jt Open 2024;5(6):464–478.